Fundraising Aspect of International Terrorism Organization in ASEAN: Legal and Political Aspects - Jamin Ginting; Patrick Talbot (Lex Scientia Law Review, 2023)
Since the Bali Bombing I and Bali Bombing II Tragedy, the seriousness of combating international terrorism have become increasingly apparent. Each member of ASEAN hand in hand together enforces both international cooperation and bilateral cooperation to prevent and counteract, through appropriate domestic measures, the financing of terrorists and terrorist organizations, whether such financing is direct or indirect through organizations. International community efforts to combat terrorism activities, not only comprise the criminalization of terrorists the act criminalization financing of terrorism, and the criminalization of terrorist financing. Since that moment, the topic of money laundering is an inherent element of organized crime, with its strong linkage to terrorism, has found and always will find new methods to satisfy the also new necessities for financing terrorism. ASEAN already make a policy about terrorism which is the convention on counter-terrorist called ASEAN Convention on Counter-Terrorism (ACCT). The convention of ACCT, in article 6 Areas of Cooperation, ASEAN emphasizes the prevention of giving the fund to the terrorist group. Indonesia had given responses to financing terrorism by ratifying The International Convention for the Suppression of the Financing of Terrorism, 1999, and subsequently with the enacted Law Number 6 Year 2006 and also enacted the new Prevention and Eradication Money Laundering Offence, Law Number 8 of 2010.